Achieving correction of a posterior scissorbite with a mini-screw. (1st January 2020) - Matharu, Jason; Macey-Dare, Lucy; Dickson, James; Farrier, Jerry
Abstract : Scissorbite correction of posterior teeth can often be challenging. For adolescent patients, they may occur due to late eruption of the second permanent molar teeth after appliances are removed, or due to operator preference not to include them on the appliance. This case report describes a 17-year-old patient who had previously been treated with fixed appliances but did not originally have second permanent molars bonded. Complete correction of the scissorbite on the UR7 was effectively achieved in 14 weeks using a minimal system comprising only a palatal mini-screw, molar band and elastomeric chain. CPD/Clinical Relevance: Mini-screws placed in a palatal position can provide an effective way to correct posterior scissorbites.